Analisis Perhitungan Harga Pokok Produksi Berdasarkan Metode Full Costing Pada Usaha Mikro (Studi Kasus UMKM Umbaring Berau) - munawaroh, siti; Taufiq, Muhammad (UKI Toraja Press, 2022)
This study aims to determine and analyze whether the calculation of the cost of production at Umbaring Berau is correct based on the full costing method. This research sample was conducted during January 2022 production activities. This type of research isa quantitative descriptive method and the data collection technique used is field research. Data collection procedures carried out were interviews, observations, documentation and library research. Sources of data used are primary and secondary data. Based on the results of the study, it can be seen that the calculation of the cost of production applied by Umbaring Berau is good based on safety, it's just that it is still not right in classifying the costs incurred for production, it would be better to refer to the full costing method